Weight gain velocity as a predictor of severe obstructive sleep apnea among obese adolescents. (30th September 2019) - Johnson, Romaine F.; Hansen, Alexander; Narayanan, Ajay; Yogesh, Ahana; Shah, Gopi B.; Mitchell, Ron B.
Abstract : Objectives/Hypothesis: To evaluate a cohort of obese adolescents with obstructive sleep apnea (OSA) to determine if increased yearly weight gain was a predictor of severe OSA. Study Design: Retrospective cohort study. Methods: Obese adolescents (body mass index percentile >95% for that age and sex based upon the Centers for Disease Control and Prevention weight classifications), ages 12 to 17 years, referred for full night polysomnography (PSG) were analyzed. We examined demographics, weight classifications, yearly weight gain from age 9 years onward, PSG data (apnea‐hypopnea index), and tonsil size. We performed a mixed‐effect linear regression model to test whether the velocity of weight gain was increased in obese patients with severe OSA when compared to those without severe OSA. Results: This study included 166 obese adolescents, 105 with and 61 without severe OSA. The average age was 14 years and was predominately male (57%) and Hispanic (44%). The regression analysis found that the yearly change in weight among obese adolescents with severe OSA was significantly higher than those without (B = 1.4, standard error = 0.50, P = .005, 95% confidence interval: 0.42–2.4). For the group with severe OSA, weight increased 6.5 kg every year before their PSG, whereas for those without, weight increased 5.1 kg per year. Conclusions: The rate of weight gain over time is an important predictor of severe OSA in obese adolescents. Level of Evidence: 3b Laryngoscope, 130:1339–1342, 2020